Studies on different oxidation behaviors of TiAlN on titanium alloy and stainless steel under thermal cycling. (November 2021) - Zhang, Mingming; Li, Yongfeng; Feng, Yipeng; Xin, Li; Niu, Yunsong; Su, Jianxiu; Zhu, Shenglong; Wang, Fuhui
Abstract: This paper aims to explore the different oxidation behaviors of TiAlN coatings on two various substrates under thermal cycling at 750 °C. Thin oxide scale layer formed and Ti2 N phase generated in TiAlN-TC4 system. IDZ composed of nitride phase appeared at TiAlN/TC4 interface after thermal cycling. By contrast, for TiAlN on stainless steel, thick oxide scale layer formed on the surface. There were no phase transitions in TiAlN and IDZ at coating/substrate interface after oxidation. The various oxidation cracking behaviors also occurred to the two systems. The relative oxidation mechanisms are discussed in detail in this study. Highlights: Various oxidation behaviors of TiAlN are studied under thermal cycling at 750 °C. The formation of IDZ and Ti2 N led to the oxidation cracking in TiAlN on TC4. No IDZ or Ti2 N formed in TiAlN deposited on stainless steel at thermal cycles. Large thermal tensile stress and high stiffness of stainless steel induced cracking.